difference of two squares
a^2-b^2 = (a+b)(a-b)
5^2-x^2 = (5+x)(5-x)
factor
(25-x^2)
4 answers
25-x^2=(5-x)*(5+x)
(5-x)*(5+x)=5*5-5*x+x*5-x^2=25-5x+5x-x^2=25-x^2
(5-x)*(5+x)=5*5-5*x+x*5-x^2=25-5x+5x-x^2=25-x^2
why is it not -(x-5)(x+5)
wouldnt you have to factor out a negative first so the x^2 isnt negative?
wouldnt you have to factor out a negative first so the x^2 isnt negative?
lou,
your answer of -(x-5)(x+5) is the same as the answer of (5-x)(5+x) that Damon and anonymous gave you
if you want to factor out the -1 at the start, you can do that
25 - x^2
= -(x^2 - 25)
= -(x+5)(x-5)
really makes no difference
your answer of -(x-5)(x+5) is the same as the answer of (5-x)(5+x) that Damon and anonymous gave you
if you want to factor out the -1 at the start, you can do that
25 - x^2
= -(x^2 - 25)
= -(x+5)(x-5)
really makes no difference